2019
DOI: 10.3389/fmicb.2019.02127
|View full text |Cite
|
Sign up to set email alerts
|

The PolS-PolR Two-Component System Regulates Genes Involved in Poly-P Metabolism and Phosphate Transport in Microlunatus phosphovorus

Abstract: Microlunatus phosphovorus NM-1 is a polyphosphate (poly-P)-accumulating bacterium that accumulates poly-P under aerobic conditions and degrades poly-P under anaerobic conditions. In this study, the two-component system (TCS) PolS-PolR was identified in NM-1, and the response regulator PolR was found to directly bind to the promoters of genes related to phosphate transport (MLP_RS00235, MLP_RS23035, and MLP_RS24590); poly-P catabolism (MLP_RS12905) and poly-P synthesis (MLP_RS23025). RT-qPCR assays showed that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…The RspA1 knock-out mutant, ΔrspA1 , in Streptomyces albus demonstrated lower biomass accumulation and lower glucose consumption rates as compared to the parental strain A30 when cultivated in a defined minimal medium (MM) complemented with 75 mM glutamate [ 24 ]. The PolS-PolR TCS, identified in Microlunatus phosphovorus NM-1, was shown to regulate polyphosphate catabolism, and the response regulator PolR was found to directly bind to the promoters of genes involved in phosphate transport [ 25 ]. These examples outline the extent to which TCS regulation is present in bacterial metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…The RspA1 knock-out mutant, ΔrspA1 , in Streptomyces albus demonstrated lower biomass accumulation and lower glucose consumption rates as compared to the parental strain A30 when cultivated in a defined minimal medium (MM) complemented with 75 mM glutamate [ 24 ]. The PolS-PolR TCS, identified in Microlunatus phosphovorus NM-1, was shown to regulate polyphosphate catabolism, and the response regulator PolR was found to directly bind to the promoters of genes involved in phosphate transport [ 25 ]. These examples outline the extent to which TCS regulation is present in bacterial metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, this is the first report that the solubilization of inorganic insoluble phosphorus is coupled with the synthesis of polyphosphate. It has been reported that polyphosphate regarded as high-energy compound could be hydrolyzed when phosphorus accumulating bacteria undergo undernourished conditions (Wan et al, 2017;Li and Dittrich, 2019;Zhong et al, 2019). Previous literatures have reported that some bacteria belonging to Acinetobacter genus harbor the ability to synthesize polyphosphate and could be regarded as phosphorus accumulating bacteria (Keating et al, 2016;Han et al, 2018).…”
Section: Deciphering Phosphorus Track During Inorganic Phosphorus Solmentioning
confidence: 99%
“…This implies that bacteria-mediated P o cycling was enhanced in the rhizosphere of these crops, although the total P o contents increased for both crops under the NB treatment ( Table 2 ). In addition, Microlunatus facilitates the formation and accumulation of polyphosphate ( Zhong et al, 2019 ). The enriched Microlunatus positively correlated with the Ca 8 -P i fraction, but negatively correlated with the Ca 2 -P i , Al-P i and Fe-P i fractions in both maize and soybean rhizospheres ( Figures 1B , 2B ), suggesting that Microlunatus may be involved in transformation of Ca 2 -P i , Al-P i and Fe-P i fractions into the Ca 8 -P i fraction through the formation of polyphosphate by Microlunatus and the subsequent hydrolysis of polyphosphate to replenish Ca 2 -P i , Al-P i and Fe-P i pools.…”
Section: Discussionmentioning
confidence: 99%